Novel stem cell technologies are powerful tools to understand the impact of human factors on Plasmodium falciparum malaria - Pance, Alena; Ng, Bee L.; Mwikali, Kioko; Koutsourakis, Manousos; Agu, Chukwuma; Rouhani, Foad J.; Montandon, Ruddy; Law, Frances; Ponstingl, Hannes; Rayner, Julian C. (Frontiers in Cellular and Infection Microbiology, 2023)
Plasmodium falciparum parasites have a complex life cycle, but the most clinically relevant stage of the disease is the invasion of erythrocytes and the proliferation of the parasite in the blood. The influence of human genetic traits on malaria has been known for a long time, however understanding the role of the proteins involved is hampered by the anuclear nature of erythrocytes that makes them inaccessible to genetic tools. Here we overcome this limitation using stem cells to generate erythroid cells with an in-vitro differentiation protocol and assess parasite invasion with an adaptation of flow cytometry to detect parasite hemozoin. We combine this strategy with reprogramming of patient cells to Induced Pluripotent Stem Cells and genome editing to understand the role of key genes and human traits in malaria infection. We show that deletion of basigin ablates invasion while deletion of ATP2B4 has a minor effect and that erythroid cells from reprogrammed patient-derived HbBart α-thalassemia samples poorly support infection. The possibility to obtain patient-secific and genetically modifed erythoid cells offers an unparalleled opportunity to study the role of human genes and polymorphisms in malaria allowing preservation of the genomic background to demonstrate their function and understand their mechanisms.